Discourse and Working Memory in Conduction Aphasia-A case study - Hema, N.a, Maharunnisa. P. (Journal of All India Institute of Speech and Hearing)
This case study describes the language processing diculties exhibited by the case with conduction aphasia with respect to the de cits in working memory capacity and discourse ability. The case presented here is the 33-year old right-handed female, who started exhibiting aphasic features following craniotomy for the anaplastic oligodendroglioma. In this case study, the medical report is presented rst followed by the description of cognitive-linguistic de cits. The tasks used in this case study were narrative discourse task and working memory tasks such as, forward span task, backward span task and N-back tasks.